Faktor-faktor yang Memengaruhi Pengambilan Keputusan Terhadap Klaim Jaminan Hari Tua: Factors Affecting Decision Making Against an Old Age Benefit Claim - Nasution, Ryan Ramanda; Sarma, Ma’mun; Sukmawati, Anggraini (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The tendency of early claim insurance for old age benefit (JHT) causes concerns in the social security system in Indonesia because it can eliminate regeneration in old age and reduce the living standards of the elderly. This study aims to analyze the influence of participants regarding the perception of JHT policy, participants trust information intervention, social security literacy, and financial literacy on the decision to postpone JHT's claims. The design of this study is a quantitative and cross-sectional study to analyze various variables in the study. The sample was determined by random sampling, with 229 respondents being active participants of BPJS Ketenagakerjaan but were detected to have made JHT claims before. Google Form is used to collect questionnaire data that is further analyzed descriptively and using Structural Equation Modeling (SEM) with the help of SMARTPLS software. Analysis using SMARTPLS obtains findings that variables that significantly positively affect decisions to delay claims are perception variables regarding policies, trust, information interventions, and social security literacy. Whereas financial literacy has no significant effect on the decision to postpone claims. Furthermore, BPJS Ketenagakerjaan as Indonesian social security bodies needs to conduct massive socialization and education to increase participants' trust and knowledge about the benefits of the JHT program if deposited so that JHT can return to the proper philosophy. Keywords: decision making, employment social security, information intervention, policy perception